Self-rated health: a study in an elderly low income population of São Paulo - Silva, Thiago Rodrigo da; Menezes, Paulo Rossi (Revista de Medicina, 2007)
Self-rated Health has been taking an important status in epidemiological research because of its strong and independent association with mortality. International papers indicate many determinants factors of self-rated health, but few studies have been carried out indeveloping countries as Brazil. This paper aims to study socioeconomic characteristics and chronic diseases associated with self-rated health. It was performed a cross-sectional study with 2,072 old aged adults over 65 years, living in an economically deprived area in São Paulocity. Socioeconomic characteristics, chronic diseases, difficulty with activities of daily living, chronic pain and common mental disorders symptoms were accessed and analyzed with apolytomic logistic regression model. We found an association of self-rated health and income,angina, stroke, chronic cough, difficulty with activities of daily living, chronic pain and common mental disorders symptoms. It was concluded that self-rated health is a consistent variable, and studies performed in developed countries have found similar results.